Construction of Information Retrieval Thesaurus on Nervous System Diseases Terms Using Prolog - Jyothi, T. (Journal of Information and Knowledge, 2014)
Thesaurus is a vocabulary control device, which improves the efficiency of information retrieval. A thesaurus provides a map of a given field of knowledge. It brings together terms that are hierarchically related. The thesaurus is constructed with the help of programming language PROLOG. The main sources of data for the construction of this information retrieval thesaurus is Medical Subject Headings (MeSH). published by the National Library of Medicine, USA. The thesaurus presented in this paper is in fact a re-formatted MeSH. The sample construction of thesaurus for the subject term "MENINGITIS" is presented.